Outskirts of empire studies in British power projection - Fisher, John 1968- (Empires in perspective, 2018)
"This book investigates the substructure of Britain's interests in the Near East and beyond during the nineteenth and twentieth centuries. Essays address themes in British power projection in a geographically wide area and highlight the network of Britons required to sustain the British presence in the Near East"--